CONSTRUCTAL THEORY: FROM ENGINEERING DESIGN TO PREDICTING SHAPE AND STRUCTURE IN NATURE - Bejan, Adrian (Revista de Engenharia Térmica, 2001)
This is a review of two new and important developments in thermal science. First, there exist fundamental optima in the constitution and operation of flow (nonequilibrium) systems, man-made and natural. These optima can be identified based on the simplest models that still retain the essential features of the real systems. Examples are the spatial allocation of heat transfer area in a power plant, and the temporal optimization of on & off processes. The second development is that the engineering method of modeling and optimization has been extended to natural systems, animate and inanimate (e.g., tree networks). This step has been named constructal theory for the reasons given in Section 3. The objective of such work is to predict the macroscopic spatial and temporal structure (organization) that is everywhere. It is to inject a dose of determinsm (theory) in a field that until recently considered natural structures to be nondeterministic: results of chance and necessity. These developments bring to mind the advice left to us by J. W. Gibbs more than one hundred years ago: "One of the principal objects of theoretical research in any department of knowledge is to find the point of view from which the subject appears in its greatest simplicity."